FORMULATING PROCESS IMPROVEMENT FOR TANDON CITRA MURTI.LTD''S TANK CONSTRUCTION PROCESS USING FAILURE MODES AND EFFECTS ANALYSIS AND DESIGN REVIEW BASED ON FAILURE MODES - Akira, Reyner
This research is about making a suggestion to improve PT. Tandon Citra Murti’s tank construction process. The company’s 7500 kL process is used as an object of this research. The purpose of this research is to: identify the main problems in the 7500 kL tank construction process of PT. Tandon Citra Murti, to establish the recommended actions that needs to be done in order to prevent the problem, and to make the improvement implementation schedule for PT. Tandon Citra Murti. Failure Mode and Effects Analysis (FMEA) is an analytical method which purpose is to identify the potential cause of problem, assessing the associated risk of the problem, the effects and cause of the problem, and also to establish the recommended actions in order to fix the problem. Design Review Based on Failure Mode (DRBFM) is a methodology developed from FMEA and is used to control the changes in the study of change management. This methodology focuses on controlling and preventing problems in an early stage. FMEA and DRBFM is used as the main methods to establish the recommended actions. DRBFM’s methodology follow the steps used in DMAIC. In Define, the construction process is mapped with work breakdown structure, potential failures happening along the process is mapped with FMEA. In Measure, scoring and choosing which failures is going to be solved, is done with FMEA and Pareto. FMEA is used as a tool to record the scoring of RPN of each failures. Pareto is used to choose the failures that is going to be solved. In Analyze, the search for the root causes of the problems are done. DRBFM is used as a tool to record the root causes and things to consider for each failures. FMEA is used as a documentation tool for the root causes. In Improve, FMEA is used as a tool to record the recommended actions. In Control, DRBFM is used to record the implementation schedule alongside party responsible for its implementation. The results of this research are: (a) 13 main problems identified within the tank construction process of PT. Tandon Citra Murti, (b) 12 recommended action will be implemented, (c) the implementation of recommended action will be done in the span of 6 weeks.